Studi Literatur : Stunting Dan Masalah Perkembangan Motorik Anak: - Erwina Sumartini, Erwina Sumartini (LPPM ITEKES Mahardika, 2023)
The Global Nutrition Report states that 22.2% of children worldwide are stunted. Stunting is a public health problem associated with an increased risk of pain, death and inhibition to growth both motor and mental. Lack of nutrient intake can directly affect the development of muscles, brain and nerves as the main factor of child development. The purpose of this study was to determine the relationship between stunting and children's motor development. The method used in writing this article is literature review through google scholar-based data. The results of the study showed that stunting has a significant relationship with children's motor development abilities, both gross motor and fine motor. Children's nutritional intake at 1000 HPK is very important to support the child's motor growth and development.